Gender Challenge of contemporaneity - O B Maximova (RUDN Journal of Philosophy, 2009)
Gender relations in modern society have their historical roots and are subject to change. The tendencies as well as the tremendous scale of transformations currently taking place both in Russia and in the West can be treated in terms of «gender challenge». The article deals with the typical trends of gender relations' transformations in the global framework as well as reveals the peculiarities of Russian gender order.